The Migration of the Warming Center and Urban Heat Island Effect in Shanghai During Urbanization - Shen, Zhongping; Shi, Jun; Tan, Jianguo; Yang, Hanwei (Frontiers in Earth Science, 2020)
Based on the monthly air temperature data from 11 national meteorological stations of Shanghai, the construction land areas derived from the Landsat Thematic Mapper (TM) data and population density data, the migration of urban warming centers in different decades since 1980s and their possible causes were analyzed, and the temporal and spatial variation characters of urban heat island (UHI) were investigated. The location of warming centers migrated from Baoshan to Pudong and then moved toward Songjiang and Nanhui. The shifting of the location of the warming center mainly depends on the growth of metropolitan construction land area and population density. The intensity of UHI displayed three stages successively: slow growth stage (1961–1986) with a growth rate of 0.13°C/10a, rapid growth (1987–2204) stage with a growth rate of 0.60°C/10a, and obvious deceleration stage (2005–2017) with a decline rate 0.43°C/10a. In the past 57 years, the intensity of UHI in the nighttime was 0.4°C greater than that of the daytime. With the accelerating process of urbanization, the UHI in Shanghai gradually expanded from the urban areas to the surrounding suburbs and even began to expand radially toward the southwest of the rural regions in the 21st century. The results can provide references for urban heatwave prediction and mitigation of the UHI effect in Shanghai.